Comparing g(x) with f(x), you can see that the function f(x) is translated to the right by 6 units to produce g(x) which is equivalent to (x-6)²
<h3>Transformation of function</h3>
Transformation is a techniques use to change the position of an object on an xy-plane.
Given the parent function f(x) = x² and the function g(x) = x²-12x +36
Factorize g(x);
g(x) = x²-6x-6x+36
g(x)=x(x-6)-6(x-6)
Group the terms to have;
g(x) = (x-6)²
Comparing g(x) with f(x), you can see that the function f(x) is translated to the right by 6 units to produce g(x) which is equivalent to (x-6)²
Learn more on transformation here: brainly.com/question/4289712
#SPJ1
Answer:
A
Step-by-step explanation:
You are right
Answer:
w=21
Step-by-step explanation: